(untitled) (Journal of Parents and Teachers, 2023)
Some teachers find students diagnosed with cancer in their classrooms. Learning to manage the situation and having the emotional resources is fundamental since they will help the student and his family to face the situation in an adapted way and that the teaching-learning process is affected as little as possible. This article proposes some guidelines and strategies that facilitate the work of the educational environment in the face of this disease.